(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Although tissue repair is an evolution of the body itself to resolve the wound, many need special care for proper healing. Medicinal plants, such as Rhizophora mangle, have a traditional use for wound healing. This study aimed to evaluate the healing potential of aqueous extract of leaves of R. mangle (AELRm) in cream for surgical wounds in rats. Forty-five Wistar rats were subjected to surgical wound care and divided into three groups of 15 animals each: Control group (saline solution at 0.9%), Standard group (dexpanthenol at 5%) and AELRm group (aqueous extract of leaves of R. mangle in cream at 5%), undergoing euthanasia on the 5th, 10th, and 15th days. Morphometric and histomorphometric studies of the wounds were performed, as well as macroscopical evaluation of them. The treated group showed uniform wounds and no infection, but the macroscopic analysis showed no difference on the 15th day among the three groups due to the rectangular shape of the initial wound. The microscopic study showed that all animals treated with AELRm in cream showed complete re-epithelialization on the 15th postoperative day (p = 0.033) in relation to the standard group (582.21 Î¼m) and Control group (968.89 Î¼m). The present study shows that the topical use of AELRm in cream at 5% has a significant effect on re-epithelialization of surgical wounds in rats.